Formulação de extrato aquoso de tremoço branco (Lupinus albus L.) adicionado de suco de pitanga utilizando metodologia de superfície de resposta - Botaro, Juliana Aparecida; Borsato, Dionisio; Batistuti, Jose Paschoal [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The aim of the present study was to verify, through the response surface methodology, the optimum conditions for the combined use of aqueous extract of white lupine (Lupinus albus L.) and tropical pitanga juice (Eugenia unifl ora L.) in the development of a drink. Therefore, the independent variables were represented by the volume of aqueous extract of lupine (mL) and by the volume of pitanga juice (mL). The dependent variables (responses) were obtained through sensory test of acceptance (“appearance”, “aroma”, “taste” and “overall acceptability”). The combined optimization of the variables pointed the second formulation (50mL of aqueous extract of lupine and 30mL of pitanga juice) of the experimental project as the most adequate. In conclusion it was possible to get a drink with attractive sensory characteristics using aqueous extract of white lupine and tropical pitanga juice. The usage of response surface methodology made possible the determination of regions of maximum acceptance for each attribute evaluated in the formulation of a drink with aqueous extract of white lupine and pitanga juice, with a minimum of tests.

O objetivo deste trabalho foi verifi car, através da metodologia de superfície de resposta, as melhores condições para a utilização simultânea de extrato aquoso de tremoço branco (Lupinus albus L.) e de suco de pitanga (Eugenia unifl ora L.) no desenvolvimento de uma bebida. Para tanto, as variáveis independentes foram representadas pelo volume de extrato aquoso de tremoço (mL) e pelo volume de suco de pitanga (mL). As variáveis dependentes (respostas) foram obtidas através de teste sensorial de aceitação (“aparência”, “aroma”, “sabor” e “impressão global”). A otimização conjunta das variáveis apontou o ensaio 2 (50mL de extrato aquoso de tremoço e 30mL de suco de pitanga) do planejamento experimental como sendo o ótimo. Pode-se concluir que foi possível obter uma bebida com características sensoriais atrativas, utilizando extrato aquoso de tremoço e suco de pitanga. O uso da metodologia de superfície de resposta possibilitou a determinação de regiões de máxima aceitação para cada atributo avaliado na formulação da bebida contendo extrato aquoso de tremoço branco e suco de pitanga com um número mínimo de ensaios.
Formulation of an aqueous extract of white lupine (Lupinus albus L.) with pitanga juice using response surface methodology
Keywords: White lupine (Lupinus albus L.); Drink development; Aqueous extract; Pitanga juice; Response surface methodology; Sensory analysis; Tremoço branco (Lupinus albus L.); Desenvolvimento de bebida; Extrato aquoso; Suco de pitanga; Metodologia de superfície de resposta; Análise sensorial